Odpowiedź :
Odpowiedź:
3)
a)
(x² + 4x)/(x² - 16) = x(x + 4)/[(x - 4)(x + 4)]
założenie
x - 4 ≠ 0 ∧ x + 4 ≠ 0
x ≠ 4 ∧ x ≠ - 4
D: x ∈ R \ { - 4 , 4 }
x(x + 4)/[(x - 4)(x + 4)] = x/(x - 4)
b)
(x² - 9)/(x² - 6x + 9) = [(x - 3)(x + 3)]/(x - 3)²
założenie :
x - 3 ≠ 0
x ≠ 3
D: x ∈ R \ {3}
[(x - 3)(x + 3)/[(x - 3)(x - 3)] = (x + 3)/(x - 3)
c)
(2x² + 6x)/(x³ - 9x) = 2x(x + 3)/x(x² - 9) = 2x(x + 3)/x[(x - 3)(x + 3)
założenie:
x ≠ 0 ∧ x - 3 ≠ 0 ∧ x + 3 ≠ 0
x ≠ 0 ∧ x ≠ 3 ∧ x ≠ - 3
D: x ∈ R \ {- 3 , 0 , 3 }
2x(x + 3)/x{x - 3)(x + 3)] = 2/(x - 3)
a)
D.
x² - 16 ≠ 0
(x + 4)(x - 4) ≠ 0
x ≠ -4 i x ≠ 4
D = R \{-4, 4}
[tex]\frac{x^{2}+4x}{x^{2}-16} = \frac{x(x+4)}{(x+4)(x-4)} = \frac{x}{x-4}[/tex]
b)
x² - 6x + 9 ≠ 0
(x - 3)² ≠ 0
x ≠ 3
D = R \ {3}
[tex]\frac{x^{2}-9}{x^{2}-6x+9} = \frac{(x-3)(x+3)}{(x-3)^{2}} = \frac{x+3}{x-3}[/tex]
c)
x³ - 9x ≠ 0
x(x² - 9) ≠ 0
x(x + 3)(x - 3) ≠ 0
x ≠ 0 i x ≠ -3 i x ≠ 3
D = R \ {-3, 0, 3}
[tex]\frac{2x^{2}+6x}{x^{3}-9x} = \frac{2x(x+3)}{x(x^{2}-9} = \frac{2x(x+3)}{x(x+3)(x-3)} = \frac {2}{x-3}[/tex]